Considering Social Equity in a New Public Management Reform: Evidence from Milwaukee, Wisconsin. (4th July 2021) - Ford, Michael R.
Abstract : This article uses the case of independent charter schools in Milwaukee, Wisconsin, to test whether New Public Management style reforms are compatible with the public administration pillar of social equity. Using three years of data, the author identifies inequities in access and outcomes due to the structural differences between charter and traditional public schools. Structural differences include governance, admissions, and transportation policies. Overall, independent charter schools serve fewer Black pupils, are less accessible, but do obtain comparatively better achievement scores. The article concludes with suggestions on how metagovernance can be used to ensure social equity in decentralized governance reforms. The study demonstrates how social equity can be analytically evaluated in a governance reform environment, and provides guidance on how structural barriers to social equity can be overcome in complex governing networks.